Factor Affecting Consumer Trust and Continuous Adoption of Online Financial Service in Kathmandu Valley - Rajbanshi, Menuka (Nepalese Journal of Business, 2024)
The study examines the factor affecting consumer trust and continuous adoption of online financial service in Kathmandu Valley. Consumer trust and continuous adoption are selected as dependent variables. The selected independent variable are website design, reliability, responsiveness, online experience, and personalization. The primary source of data is used to assess the opinions of the respondents regarding website design, reliability, responsiveness, online experience, personalization and adoption of online financial services. The study is based on primary data of 400 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors on consumer trust and continuous adoption of online financial service in Kathmandu Valley. The study showed that website design has a positive impact on consumer trust and continuous adoption. It means that better website design leads to continuous adoption of financial services. Likewise, reliability has a positive impact on consumer trust and continuous adoption. It shows that increase in reliability leads to continuous adoption of financial services. Furthermore, responsiveness has a positive impact on consumer trust and continuous adoption. It indicates that increase in responsiveness leads to continuous adoption of financial services. In contrast, online experience has a positive impact on consumer trust and continuous adoption. It indicates that better online experience leads to continuous adoption of financial services. Similarly, personalization has a positive impact on consumer trust and continuous adoption. It indicates that better facilities of personalization lead to continuous adoption of financial services.